Analysis of pedestrian-vehicle crossing interaction - Soares, Francisco Emanuel Cunha (2019)
A big focus has been given to soft modes of transportation. In this way, it is necessary to create the best safety conditions for those who are the most vulnerable users of the road network, with the greatest emphasis to pedestrians. The main goal of this work is to identify the factors which contribute to risk-taking behavior by these road users, by analyzing pedestrian’s crossing behavior using data collected through video recordings in real crosswalks and the execution of experiments in a virtual environment. First results show that the proximity of the bus stops to the crosswalk, the width of the street occupied by parking spaces and the average width of the sidewalks, the crosswalk width and the pedestrian traffic volume were the variables with significant impacts on the vehicle-pedestrian interaction.